Producción de multimedia: una experiencia en el campo de las matemáticas - Chavarría, Jesennia (2008)
The objective of this paper is to describe an experience with a multimedia application, intended for students of secondary school. We propose a collection of methodological elements to design, elaborate and evaluate multimedia products. This experience shows how teachers could play a key role in the generation of multimedia products assuming current technical and didactical standards.